The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1440-1754.2004.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal foreign bodies

Abstract: In the majority of patients a carefully obtained history and physical examination suggest the diagnosis of a vaginal foreign object. The leading symptoms are vaginal bleeding and blood-stained or foul smelling vaginal discharge. Removal of the foreign object followed by a single irrigation with Providon-Iod is the definitive treatment and does not require additional measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 7 publications
2
65
1
4
Order By: Relevance
“…Stricker et al (5) reported that 49% of girls with a vaginal foreign body had presented with vaginal discharge. Also, a study review performed by Striegel et al (6) reported that the etiology of vaginal discharge in girls younger than 6 years who underwent examination under general anesthesia in 45% of the cases was foreign bodies in the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Stricker et al (5) reported that 49% of girls with a vaginal foreign body had presented with vaginal discharge. Also, a study review performed by Striegel et al (6) reported that the etiology of vaginal discharge in girls younger than 6 years who underwent examination under general anesthesia in 45% of the cases was foreign bodies in the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive treatment of vaginal foreign bodies requires removal of the foreign body, in humans as well as in dogs (Stricker 2004;Snead et al 2010). Foreign bodies located in the distal vagina may be removed manually or with forceps, while foreign bodies more cranial or embedded in the vaginal wall require vaginoscopic-guided retrieval (Ratcliffe 1971;Dietrich 1979;Soderberg 1986;Jacobs et al 1989;Johnston et al 2001;Feldman and Nelson 2004;McCabe and Steffey 2004;Stricker 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies located in the distal vagina may be removed manually or with forceps, while foreign bodies more cranial or embedded in the vaginal wall require vaginoscopic-guided retrieval (Ratcliffe 1971;Dietrich 1979;Soderberg 1986;Jacobs et al 1989;Johnston et al 2001;Feldman and Nelson 2004;McCabe and Steffey 2004;Stricker 2004). Ultrasound-guided retrieval of vaginal foreign bodies has been described in a bitch and in a queen (Gatel et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La presencia de cuerpos extraños vaginales se produce habitualmente en la etapa preescolar o escolar debido a la automanipulación de los genitales (1,2). En mujeres adultas es menos frecuente, pero se han descrito en relación con maniobras sexuales (3-6) asociadas a alta morbilidad secundaria (fístulas vesicovaginales y/o ureterovaginales) (5).…”
Section: Introductionunclassified